Frequent Participation in Service Learning: Examining Institutional Differences and Individual Benefits. Issue 162 (December 2014) - Bureau, Daniel A.; Cole, James S.; McCormick, Alexander C.
Abstract : This chapter examines the differences between institutions with high and low levels of involvement in service learning as well as the differences between students with high and low levels of involvement. The study shows a correlation between institutional organization and service‐learning emphasis and describes, at the student level, correlations between service‐learning involvement and both deep approaches to learning and self‐reported gains.